DISTRIBUTION OF AUTHORITIES OF FOREST MANAGEMENT THROUGH COMMUNITY JOINT FOREST MANAGEMENT PROGRAMS FROM THEORY OF LEGAL OBJECTIVES AND THE DEMOCRACY CONCEPT IN THE AREA - Anajeng Esri Edhi Mahanani; Eko Wahyudi; Rohmatul Rohmatul (Surakarta Law and Society Journal, 2019)
This paper aims to analyze and review policies and arrangements for the distribution of power or authority in forest management through the Collaborative Forest Management program. Furthermore, the policy of distribution of management authority will also be analyzed in terms of legal objectives, namely legal certainty, benefits and justice. Based on the results of the discussion it can be said; First, that normative arrangements and policies on forest management programs through the distribution of power or authority constitute a form of fulfillment of Law No. 41 of 1999 concerning Forestry, Government Regulation of the Republic of Indonesia about Forest Arrangement and Preparation of Forest Management Plans, and Forest Utilization, up to the Decree of the Directors of Perum Perhutani No: 268 / KPTS / DIR / 2007 concerning Guidelines for Managing Joint Forest Resources Plus (PHBM PLUS). Second, this policy of distribution of authority or power embodies the benefits of the law, when viewed from the principle that the law is for humans. Third, to create social justice, forest management with the community will help realize the spirit of Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia, not only for local forest village communities but also for more evenly distributed Indonesian society